2021
DOI: 10.1371/journal.pone.0256394
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for COVID-19 vaccine distribution strategies in the US: A discrete choice survey

Abstract: Background The COVID-19 vaccination campaign in the US has been immensely successful in vaccinating those who are receptive, further increases in vaccination rates however will require more innovative approaches to reach those who remain hesitant. Developing vaccination strategies that are modelled on what people want could further increase uptake. Methods and findings To inform COVID-19 vaccine distribution strategies that are aligned with public preferences we conducted a discrete choice experiment among t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 29 publications
4
39
1
Order By: Relevance
“…Furthermore, these types of passports must not be used to discriminate and eliminate the unvaccinated from society, allowing them to use alternative services, such as a certificate for a negative COVID-19 test result. Requiring these types of passports to re-engage in social activities may essentially violate the freedom of choice,31 which could be why some studies suggest that this type of scheme was viewed as negative 33 34. Given the potential health risks of vaccination, it may not be feasible to mandate vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, these types of passports must not be used to discriminate and eliminate the unvaccinated from society, allowing them to use alternative services, such as a certificate for a negative COVID-19 test result. Requiring these types of passports to re-engage in social activities may essentially violate the freedom of choice,31 which could be why some studies suggest that this type of scheme was viewed as negative 33 34. Given the potential health risks of vaccination, it may not be feasible to mandate vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Requiring these types of passports to re-engage in social activities may essentially violate the freedom of choice, 31 which could be why some studies suggest that this type of scheme was viewed as negative. 33 34 Given the potential health risks of vaccination, it may not be feasible to mandate vaccination. In Japan, there is no vaccine mandate, not only for COVID-19 but for other diseases, while some of these are determined by law as non-binding obligations of the citizens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess whether information campaigns reduce hesitancy, studies are needed that examine their impact on vaccination intention and vaccination actions over time. Beyond these interventions, the convenience of vaccination—such as ease of access and availability—is suggested to reduce hesitancy as well [ 46 , 47 ]. Moreover, vaccination reminders have been shown to increase COVID-19 vaccination rates [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…While vaccine brand preference has not been considered among unhoused people, a study of American adults found that vaccine brand was not associated with willingness to get vaccinated [ 12 ]. However, characteristics that may be related to vaccine brand were associated with willingness to get vaccinated: vaccine efficacy, risk of side effects, FDA approval, cost, and number of doses [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%